Penerapan Metode TOPSIS Dalam Penentuan Wali Kelas - Rajib Ghaniy; Adianti Putri Sudrajat (Universitas Binaniaga Indonesia, 2022)
The homeroom teacher has a function as a teacher who is responsible as a guardian or substitute for the parents of students while in the school area and also helps students in the academic field. As a teacher or homeroom teacher is one of the determining factors for the success of any educational effort. The teacher's ability to plan and implement learning is a major factor in achieving teaching objectives. Mastery skills in the learning process are closely related. Every year students who will enter higher education or junior high school (SMP), need to be guided and prepared carefully, so that these students can enter junior high school (SMP) according to their wishes and expectations. Therefore, it is necessary to prepare a grade 6 homeroom teacher who can guide and prepare students as well as possible during preparation for entering junior high school (SMP). So far, the determination of the 6th grade guardian is still done subjectively, the subjective referred to is an assessment based on proximity to the principal, in this case the principal also does not have definite criteria in determining the 6th homeroom teacher. To overcome the problems that occur, the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method will be applied as a tool in determining homeroom 6th graders in elementary schools. This method will determine the assessment criteria with the following criteria: Pedagogics (Knowing the characteristics of students, mastering learning theory and learning principles, assessing and evaluating learning), attendance and tenure. From the results of the application of the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method, it is to determine the 6th grade homeroom teacher in elementary school with 3 names in the top positions who will become 6th grade homeroom teachers in elementary schools. With the percentage of eligibility for information systems experts of 95% and the percentage of user eligibility of 94%.